COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE AND STOCK PRICES BEFORE AND AFTER ACQUISITION - Fatma Ade Noviana; Sri Luayyi; Anggraini, Ninik; Selviasari, Rike (Politeknik Negeri Malang, 2025)
The purpose of this study to examine the differences in financial performance and stock prices before and after acquisitions in non-banking companies listed on the Indonesian Stock Exchange (IDX) from 2018 to 2024. The research population consists of companies that made acquisitions in 2021, with 7 companies chosen as a sample through purposive sampling. Financial performance was assessed using the CR, ROA, DAR, DER, and TATO ratios, while stock price were observed from the closing price recorded at the end of the period. Data were processed through the Wilcoxon Signed Rank Test with the assistance of SPSS 25 software. The results showed that the companies financial performance differed significanly between pre-acquisition and post-acquisition periods, while the stock price revealed no significant variation across the two periods.